Atria in the Backpack, From Classroom to Convention: Reflections on the Conceptual Evolution of Higher Education as a Social Right - Paz Coronel, Daniela Patricia (Ius Humani. Jornal do direito, 2024)
This paper aims to conduct a descriptive analysis about the conceptual development that Chilean higher education has had from the perspective of Fernando Atria. We will use his texts; " Neoliberalism con rostro Humano" (2013) and " Derechos Socials and Education" (2014), as a starting point. They will be contrasted with some more up-to-date interviews, to determine the existence of any meaningful change around his higher education concept towards a context pre and post social outbreak (October 2019). Thus, it is of special significance to make reflections around the public discussion that involves the new Chilean constitution drafting, where Atria also won its seat as a conventional constituent. Therefore, it is sought in this process to show his transition from academic to political.